The Legality of Land Clearance and Relocation for the Rempang Eco City National Strategic Project in Light of Law Number 2 of 2012 on Land Acquisition - Markus Gunawan; Erniyanti; Fadlan (CV. RADJA PUBLIKA, 2025)
The Rempang Eco City National Strategic Project (PSN) in Batam triggered an agrarian conflict when the authorities attempted to clear and relocate residents of sixteen Malay traditional villages (Kampung Tua). The land clearance was framed as a relocation based on the Management Rights (HPL) of BP Batam rather than as land acquisition under Law Number 2 of 2012, raising the question of its legal validity. This study addresses two questions: (1) is the land clearance for the Rempang Eco City project legally valid under Law Number 2 of 2012; and (2) what legal protection is available for the affected communities. The research employs a normative juridical method with statutory, case, and conceptual approaches, using primary legal materials (legislation and official findings) and secondary materials (journals and books), analysed prescriptively and qualitatively. The findings show three legality defects. First, the project is predominantly investment, industrial, and commercial in character and is developed by a private entity (PT Makmur Elok Graha), so it does not squarely fall within the limitative